Geotechnical basis of design and early cave performance at Hugo North Lift 1, Oyu Tolgoi - Rwodzi, L.; Ekkerd, J.; Simanjuntak, K.; Baasanjav, B.; Ooi, J. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The Hugo North Lift 1 (HNL1) block cave at Oyu Tolgoi is a large‑footprint, deep (~1,300 m) cave developed in a structurally complex porphyry copper–gold system under high in situ stress conditions (σ₁ ≈ 57.8 MPa) and fair-to-poor rock mass quality. Panel 0, the first of four planned mining blocks, was undercut between 2022 and 2024 and has successfully propagated to surface, providing a unique performance dataset for block caving at this depth and stress regime. This paper documents the geotechnical basis of design (BoD) for HNL1, including the design evolution from feasibility through execution and key refinements to footprint geometry, advanced undercutting methodology, cave initiation criteria and macroblock sequencing. Panel 0 performance is then assessed against BoD predictions, with observed outcomes used to validate design assumptions and extract key learnings. Results demonstrate alignment between predicted and observed cave behaviour, including undercut advance rates, cave initiation hydraulic radius, infrastructure performance and successful full-height cave propagation. The combined BoD and performance record establishes a benchmark technical reference for the design and operation of deep, high‑stress porphyry block caves and provides guidance for reducing geotechnical uncertainty in future large‑scale cave mining projects.